PLEKHA7: Cytoskeletal adaptor protein at center stage in junctional organization and signaling. (June 2016) - Shah, Jimit; Guerrera, Diego; Vasileva, Ekaterina; Sluysmans, Sophie; Bertels, Eva; Citi, Sandra
Abstract: PLEKHA7 is a recently characterized component of the cytoplasmic region of epithelial adherens junctions (AJ). It comprises two WW domains, a pleckstrin-homology domain, and proline-rich and coiled-coil domains. PLEKHA7 interacts with cytoplasmic components of the AJ (p120-catenin, paracingulin, afadin), stabilizes the E-cadherin complex by linking it to the minus ends of noncentrosomal microtubules, and stabilizes junctional nectins through the newly identified interactor PDZD11. Similarly to afadin, and unlike E-cadherin and p120-catenin, the localization of PLEKHA7 at AJ is strictly zonular (in the zonula adhaerens subdomain of AJ), and does not extend along the basolateral contacts. Genome-wide association studies and experiments on animal and cellular models show that although PLEKHA7 is not required for organism viability, it is implicated in cardiovascular physiology, hypertension, primary angle closure glaucoma, susceptibility to staphylococcal α-toxin, and epithelial morphogenesis and growth. Thus, PLEKHA7 is a cytoskeletal adaptor protein important for AJ organization, and at the center of junction-associated signaling pathways which fine-tune important pathophysiological processes.